PROFITABILITY RATIO ANALYSIS AT PT. ACE HARDWARE INDONESIA TBK YEAR 2016-2020 - Hamdiah; Nurul Azizah; Herlina; Indah Antasari (RADJA PUBLIKA, 2023)
This study aims to determine and analyze the financial performance of PT. Ace Hardware Indonesia Tbk by using profitability ratio. The analysis method used in this study is descriptive analysis. The source of this research data is documentation in the form of annual financial statements of PT. Ace Hardware Indonesia Tbk during 2016 to 2020. This research uses a descriptive research approach, Based on the results of analysis and discussion, financial performance at PT. Ace Hardware Indonesia Tbk is measured using profitability ratios in Return on Assets on average of 16.5% in poor conditions and below industry standards of 30% and Average Return On Equity of 20.8% in poor conditions and below industry standards of 40%.